Historical demography of freshwater mussels (Bivalvia: Unionidae): genetic evidence for population expansion and contraction during the late Pleistocene and Holocene. (6th January 2015) - Jones, Jess W.; Neves, Richard J.; Hallerman, Eric M.
<x xml:space="preserve">Abstract</x> Genetic variation was examined in two endangered mussel species, Epioblasma brevidens and Epioblasma capsaeformis, and in a non‐listed species, Lampsilis fasciola, in the Clinch River, Tennessee, USA, by screening mitochondrial DNA (mtDNA) sequences and nuclear DNA microsatellites. Patterns of mtDNA polymorphism exhibited different trends in long‐term population sizes for each species during the late Pleistocene and Holocene (∼20 000 ya to present); namely, E. brevidens has declined over time, E. capsaeformis has remained demographically stable, and L. fasciola has expanded. However, analyses using microsatellites did not exhibit similar trends, perhaps because homoplasy had eliminated long‐term population signatures for the loci examined. For both marker types, long‐term effective population size (Ne) was low in E. brevidens, intermediate in E. capsaeformis, and high in L. fasciola. Moderately diverged mtDNA lineages, perhaps indicative of secondary contact, were observed in E. brevidens and E. capsaeformis. Perhaps the most surprising result of this study was the high level of genetic variation observed at both mtDNA and microsatellite DNA markers for L. fasciola, variation seemingly contrary to the relatively small demes that currently reside in the Clinch River. However, the data are consistent with known demographic and life‐history traits of these three mussel species and their fish hosts, namely that they each use hosts with different dispersal capabilities, ranging from low, moderate, and high, respectively. The low divergence of mtDNA sequence variation reported in this and other recent mussel studies indicates that considerable extant population genetic variation probably originated during the late Pleistocene and Holocene. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 376–397.